As tecnologias da informação e comunicação no ensino de gravitação : implicações sobre a prática pedagógica e aprendizagem de estudantes - Polonine, Thiago Araujo (2014)
We start from the point that the scientific knowledge is socially built, validated and communicated and that the learning process in science happens through enculturation instead of through discovery. Notwithstanding, despite this process involving social interaction, we strive for a method in which the subject understands, on a personal level, the different ways of seeing the world. Using the same perspective, for the taking of scientific conscience of students, it is essential that an intervention and negotiation happen, through argumentative practices, encouraging the students to develop new knowledge schemes that adapt better to the pedagogic experiences that they’ve had. This way, the group discussion activities make up the essence of this practice. Using this perspective, we developed and implemented a Pilot Project in 2012, proposing the use of the Facebooksocial network in the physics teaching. Given the positive reaction of the students, we built a Teaching Unit about the theme of Gravitation, where we studied its effects on the student’s learning. We structured it with activities that make up some of the main multimedia digital contents used these days in the science teaching such as animations, simulations, videos and different internet resources like social networks, where we used the fillers proposed by Vieira; Nascimento (2009) looking for evidences of the argumentative practice. The full length application of the learning unit happened in the first trimester of 2013 in four classes of the first gradeof high school at EEEFM ‘Ary Parreiras’ (SEDU). The results presented show indication of appropriation of the scientific concepts explored in the activities in most cases. We interpreted this evidence as a result of the negotiation of new meanings empowered by the proposed educational environments in our investigation; in a dialogical process that involved conversation, introducing the subjects to a new culture. We also verified indications that point to the alternative conceptions that persisted until theend of the educational experience, plausible for a formation process still in progress. Relating to the Facebookdebate activity, we verified the viability of using the fillers proposed by Vieira; Nascimento (2009) in the search for argumentative practiceevidences. Our analysis also indicated that there is a need for mediation in a practice of this nature, aiming that there is a bigger meaning negotiation between the subjects, empowering the intended scientific enculturation process. As a product of this investigation, we built a Notebook concerning the activities developed during the educational research. This way, we hope to make it possible that the present material can me used by physics teachers that intend to experiment the technologic bias in the Gravitation teaching and corresponding concepts.